Cerium-based coordination polymers micro/nanostructures: Room temperature synthesis and their thermolysis to ceria. Issue 5 (4th April 2017) - Wang, Lei; Zou, Honghong; Li, Yuan; Li, Xiaoping; Zhong, Shengliang
ABSTRACT: In this presentation, several cerium-based coordination polymers micro/nanostructures such as nanoparticles, nanorods, and microflowers were successfully prepared by a facile room temperature method using three isomers of benzenedicarboxylic acid as organic building block and Ce 3+ as center metal ion. It turns out that the three products exhibit obviously different morphologies. Also, their crystal structures are different. Amorphous products were obtained when benzene-1, 2-dicarboxylic acid was used. However, well-crystallized products were obtained with the other two isomers. After calcining at high temperature, ceria with retained morphologies were achieved. Various measurements were used to characterize the products and their UV absorption properties were studied.